Ekonomi Masjid: Studi Baitul Maal Wa Tamwil (BMT) Kota Solok - Ilhamdi Yusra (Tarikhuna: Journal of History and History Education, 2022)
This paper aims to discuss how the mosque's economy is through Baitul Maal wa Tamwil (BMT) Solok City. Solok City BMT is a non-governmental organization in the economic field and has become an icon of Solok City in order to realize the mission of Solok City, which is to become the "Kota Beras Serambi Madinah". This article uses historical research methods with data collection techniques through heuristics, source criticism, interpretation, and historiography. The results showed that the management of BMT was carried out voluntarily, institutionally this institution was not a legal entity and its members were active members of the local mosque. Regarding the activities of the Solok City BMT, it is only limited to borrowing and collecting funds and does not have financial service products like those of other microfinance institutions.